1999
DOI: 10.1046/j.1475-1313.1999.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the management of 323 consecutive patients seen in a specific learning difficulties clinic

Abstract: Visual correlates of specific learning difficulties (SpLD) include: binocular instability, low amplitude of accommodation, and Meares-Irlen Syndrome. Meares-Irlen Syndrome describes asthenopia and perceptual distortions which are alleviated by using individually prescribed coloured filters. Data from 323 consecutive patients seen over a 15 month period in an optometric clinic specialising in SpLD are reviewed. Visual symptoms and headaches were common. 48% of patients were given a conventional optometric inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 20 publications
0
43
0
Order By: Relevance
“…24,34,35,54,62 We found that introduction of an individualized colored overlay improved reading rate significantly in the high-PRVS group but not in the low-PRVS group (Fig. 3), providing further validation of the idea that rate-of-reading improvement with overlay may serve as a "proxy" diagnostic test for the existence of visual stress.…”
Section: Rate-of-reading and Colored Overlaysmentioning
confidence: 60%
“…24,34,35,54,62 We found that introduction of an individualized colored overlay improved reading rate significantly in the high-PRVS group but not in the low-PRVS group (Fig. 3), providing further validation of the idea that rate-of-reading improvement with overlay may serve as a "proxy" diagnostic test for the existence of visual stress.…”
Section: Rate-of-reading and Colored Overlaysmentioning
confidence: 60%
“…Our mean MAA values did not differ statistically among the school grades examined, neither for the poor readers or the control children, despite the steady reduction with age observed by Jimenez et al [18] (Table 2). Significant correlation between reading problems and a low amplitude of accommodation have been reported [4,5]. Thus, Evans et al [24] detected a significantly lower amplitude of accommodation in a group of dyslexic children (n = 39) than in their control group (n = 43).…”
Section: Discussionmentioning
confidence: 95%
“…Even if a child shows subjective symptoms when reading, this is often not the primary function tested in an examination. Significant correlation between reading problems and low amplitude of accommodation [4,5] and accommodative facility have been reported [6][7][8]. On the other hand, several authors have observed no statistical relationship between accommodative function and academic performance [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…An audit of a clinical population found that one-and-a-half years after patients had been prescribed precision tinted lenses, 73% were still using them on a daily basis (Evans et al, 1999). In the open trial of precision tints by Maclachlan et al (1993), a similar figure of 81% was obtained.…”
mentioning
confidence: 89%
“…In the open trial of precision tints by Maclachlan et al (1993), a similar figure of 81% was obtained. Patients' perceptions of the benefit they received from their precision tints compared favourably with other interventions, with nearly 80% reporting that tints improved their problems or difficulties (Evans et al, 1999).…”
mentioning
confidence: 99%